Understanding Financial Inclusion Through Fintech: A Qualitative Inquiry into the Role of Technology in Shaping Financial Landscapes - Idris, Hariany (Manunggal Halim Jaya, 2025)
Financial inclusion, propelled by the advent of financial technology (fintech), has become a focal point of research and policy discourse globally. This study aims to comprehensively examine the role of technology in shaping financial landscapes and fostering inclusive financial ecosystems. Employing a quantitative descriptive research approach, this study assesses fintech adoption across diverse demographic groups, identifies determinants influencing individuals' utilization of fintech-based financial services, examines the impact of fintech interventions on enhancing financial inclusion metrics, and explores the socio-economic implications of fintech-driven financial inclusion initiatives. Drawing upon a robust literature review, this research elucidates the transformative potential of fintech in expanding financial access and improving financial resilience among underserved populations. The findings underscore the importance of regulatory clarity, cybersecurity measures, and technological literacy in harnessing the full potential of fintech for inclusive economic development.